Fragments of Modernity / Theories of Modernity in the Work of Simmel, Kracauer and Benjamin - Frisby David (Policy Press, 1985)
The book provides both a critical introduction to their work and an insightful appraisal of the methodological problems that confront a social theory of modernity. Acknowledgements, Introduction, Modernite, Georg Simmel: Modernity as an Eternal Present, Siegfried Kracauer: Exemplary Instances' of Modernity, Walter Benjamin: Prehistory of Modernity, Conclusion, Notes, Bibliography, Index.